Evaluation of Zn: WO3 Thin Films as a Sensing Layer for Detection of NH3 Gas - Anusha; Priyanka Kumari; P. Poornesh; Saikat Chattopadhyay; Ashok Rao; Suresh D. Kulkarni (Micromachines, 2023)
Pristine WO3 and Zn-doped WO3 were synthesized using the spray pyrolysis technique to detect ammonia gas. The prominent orientation of the crystallites along the (200) plane was evident from X-ray diffraction (XRD) studies. Scanning Electron Microscope (SEM) morphology indicated well-defined grains upon Zn doping with a smaller grain size of 62 nm for Zn-doped WO3 (Zn: WO3) film. The photoluminescence (PL) emission at different wavelengths was assigned to defects such as oxygen vacancies, interstitial oxygens, localized defects, etc. X-ray Photoelectron spectroscopy (XPS) studies confirmed the formation of oxygen vacancies in the deposited films. The ammonia (NH3) sensing analysis of the deposited films was carried out at an optimum working temperature of 250 °C. The sensor performance of Zn: WO3 was enhanced compared to pristine WO3 at 1 ppm NH3 concentration, elucidating the possibility of the films in sensing applications.